Argentina, view of Monte Olivia from Ushuaia - Forman, Harrison, 1904-1978 (1954)
Ushuaia - Mt. Olivia (Elev. 4,495 feet) at stinger tip of S. [South] America, 60 miles from Cape Horn, 450 miles from Antarctica. Color Box 7